Pelatihan Penggunaan Media Sosial Sebagai Sarana Promosi Dojo Karate Kenbu Semarang - Masine Slahanti; Maria Augustine Graciafernandy; Helmi Yuhdana Haryanto (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
Sport has become a lifestyle for Indonesian people, with various kinds of sports that people choose as a sport of choice and achieve achievements, one of which is the sport of karate. Analysis of the current situation of sports can also be used as a business and one of the efforts to advance it is the need for a marketing strategy, one of which is promotion. Social media is one part that can easily be used as a means of promotion in the form of advertisements, content and even videos that can be shared making it easier for the public to receive information directly from business actors, including business actors, as well as fostering athletes who can later make achievements through sports. The sophistication of social media has not been fully utilized by the Semarang Kenbu Karate Dojo.